Analisis Dampak Aktivitas Masyarakat Terhadap Kawasan Lindung Kampwolker, Distrik Heram, Kota Jayapura - Franklin A. Wakom; Tommi Tommi; Sudiro Sudiro; Irja Tobawan Simbiak; Lazarus Ramandei (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Kampwolker is one of the areas included in the Cyclops nature reserve, therefore all components of the ecosystem need to be protected and their development occurs naturally. However, nowadays there have been community activities that have caused land changes. The research method used in this research is mixed method and there are two data analysis techniques used, namely, overlay data analysis techniques and quantitative data analysis techniques. Overlay data analysis can produce land changes that increase every year, while quantitative data analysis techniques can produce community activities that have an impact on the Kampwolker protected area and efforts to overcome these problems. Land changes occur due to community activities. The impact is that the water discharge has decreased so that the Kampwolker river experiences drought.